The Implementation of Sustainable Finance: A Case Study in Bank Performance - Alessandro, Andreas (AIBPM Publisher, 2023)
The idea of sustainability was risen according to climate change since the beginning of industrialization in the 18th century. As consequence, the effect will be physical disasters that lead to disadvantages for businesses. The role of banking as an intermediary makes it an agent of trust. Thus, the proper business conduct of its practice is an obligation. Attempts for green finance can be seen by the SRI KEHATI index which has the 25 most favorable issuers that mostly apply ESG criteria. This study conducts an analysis of KBMI 4 banks and then analysis the relation of ESG score compared to the financial performance, i.e NPM, ROA, and ROE from the 2017 to 2021 periods. The result shows that there is a correlation between the performance indicated by the ESG score to the financial performance of each issuer. The results showed that ESG and NPM, ROA, and ROE do not have significant relation. It was because there was no direct correlation between the ESG and the independent variables. Both, ESG and independent variables are indicators of a company’s performance. Needs further study to connect those two to find how strong the scoring is affecting a company’s performance, especially in the profitability ratio. Keywords: Banking, ESG, Green Finance, NPM, ROA, ROE, SRI KEHATI Index, Sustainability.